2011
DOI: 10.5007/1980-0037.2010v12n4p269
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação sérica de danos musculares e oxidativos em atletas após partida de futsal DOI: 10.5007/1980-0037.2010v12n4p269

Abstract: Resumo -O futsal é uma modalidade esportiva que requer súbita aceleração e desaceleração com brusca mudança de direção. Este esporte expõe seus praticantes a grandes impactos, causando danos musculares e oxidativos. O objetivo desta pesquisa foi avaliar os níveis séricos de marcadores de danos musculares e oxidativos em atletas após jogo de futsal. Participaram do estudo, seis atletas de futsal, com idade média (21,2 ± 0,98 anos), peso (67,1± 5,5 kg) e altura (171,0 ± 0,07 cm). As coletas foram obtidas 30 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
5
1
4
Order By: Relevance
“…The absolute post-match CK values found in the present study were lower than the average values normally found in soccer and futsal 28 players, which are between 350 and 400 U/L 5,6,27 . These values correspond to the normal daily physical demand of soccer players throughout a season, but they are considered high for nonathletes, as studied by Mougios 29 .…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The absolute post-match CK values found in the present study were lower than the average values normally found in soccer and futsal 28 players, which are between 350 and 400 U/L 5,6,27 . These values correspond to the normal daily physical demand of soccer players throughout a season, but they are considered high for nonathletes, as studied by Mougios 29 .…”
Section: Discussioncontrasting
confidence: 51%
“…CK, however, showed an increased post-match concentration. Changes in CK concentrations after training or soccer matches have been shown by several authors 5,6,10,27,28 . The present study disagrees with other studies, such as the one by Pimenta et al 10 , which found changes in alphaactin concentrations in soccer players, but evaluated them after a sequence of standardized eccentric muscle actions to simulate the demands of the game.…”
Section: Discussionmentioning
confidence: 97%
“…Os atletas de futsal estão propensos a diversas lesões osteomioarticulares e a utilização da crio é bastante frequente na recuperação dessas lesões. Entretanto, encontram-se poucos artigos relacionados com a crio pré-atividade 15,16 .…”
Section: Introductionunclassified
“…Souza et al 36 found rest CK values in adult indoor soccer athletes of 256.1 ± 23.6U/L, while after the end of the first and second matches, the values found were 372.6 ± 53.4 and 408.8 ± 68.8U/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be justified by the direct correlation of this enzyme and the individual characteristics of the athlete, and also by the blood peak moment after exertion 43 . The increase in the CK activity may remain for up to 72h after exercise 18,36 . Significant difference was found in the muscular temperature gradient (temperature 24h after training -temperature before training) between the control and experimental groups.…”
Section: Discussionmentioning
confidence: 99%